2022
DOI: 10.1007/s43657-022-00076-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Tau Precipitation in Alzheimer’s Disease According to ATN Research Framework

Abstract: Tau proteins accumulation and their spreading pattern were affected by gender in cognitive impairment patients, especially in the progression of Alzheimer's disease (AD). However, it was unclear whether the gender effects for tau deposition influenced by amyloid deposition. The aim of this study was to investigate gender differences for tau depositions in Aβ positive (A + ) subjects. In this study, tau and amyloid positron emission tomography images, structural magnetic resonance imaging images, and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…During the development of AD, various longitudinal biomarkers and cognitive measurements present a unidirectional ordinal pathway [11], [12] based on the Aβ, tau, and neurodegeneration (A/T/N) biomarker classification system [13], [14], [15], as shown in Fig. 1(a-b).…”
Section: Introductionmentioning
confidence: 99%
“…During the development of AD, various longitudinal biomarkers and cognitive measurements present a unidirectional ordinal pathway [11], [12] based on the Aβ, tau, and neurodegeneration (A/T/N) biomarker classification system [13], [14], [15], as shown in Fig. 1(a-b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AI can facilitate junior physicians training by providing immediate diagnostic feedback 47 . A collaborative human-AI model could optimize diagnostic accuracy by integrating the unique strengths of both components and potentially incorporating nonimagebased patient data such as demographic information and history of motor impairment [48][49][50] . These AI methods, with their potential for quality assurance and personalized, predictive medicine, represent promising models for improving healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Women may have intrinsic susceptibilities to the disease, including hypertension, menopause, pregnancy disorders, hormone therapy, and gynaecological surgeries (Cui et al ., 2023 ). Tau depositions significantly increased in females in some brain regions in Aβ positive patients (Zhang et al ., 2022 ). Epidemiological studies have reported that higher education years are associated with a reduced risk of incident AD, suggesting that education may provide protection against the onset of AD (Cho et al ., 2015 ; Scarmeas et al ., 2006 ).…”
Section: Discussionmentioning
confidence: 99%